Pengembangan Branding Melalui Konten Instagram, Katalog Dan Stiker Label Untuk Meningkatkan Penjualan Produk UD ALINDRA (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This journal discusses the strategies applied to develop branding for Micro, Small, and Medium Enterprises (MSMEs) UD ALINDRA by updating the design of catalogs, label stickers, and Instagram content. The aim of this research is to enhance the effectiveness of promotion, marketing, and product sales for these MSMEs. The method employed involves interviews with the owners of MSME UD Alindra to gain in-depth knowledge about consumer perceptions and the current branding strategies, analyzing existing challenges, and planning for production, promotion, and design updates. Through a creative approach in designing product catalogs, eye-catching label stickers, and Instagram content that aligns with trends and consumer needs, it is expected that this research will significantly contribute to increasing product sales margins, optimizing MSME owners' understanding of strong and effective branding strategies, and reinforcing their awareness of the positive impact gained from product branding, including enhancing consumer appeal and the product image for MSMEs. The results of this study indicate that the implemented developments positively contribute to the promotion of products from MSME UD ALINDRA and offer valuable insights for MSME owners to improve and enhance their product branding strategies.